Training Needs for Arabic Speakers for Non - Arabic Speakers ((Field study in the institutes of teaching Arabic language for non-speakers in Damascus)) - Rahma, Aziza; Al-Ash, Mahdi; Hoseen, Zenab (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed to identify the training needs of Arabic language teachers and to investigate the effect of each of the gender variables and the years of experience in assessing these needs by applying a questionnaire consisting of (16) words to the sample of (50) teachers and And the use of appropriate statistical programs. The results of the study showed that the degree of appreciation of the training needs of the teachers of the Arabic language for non-native speakers was high, Showed no statistically significant differences in the degree of appreciation of the study sample individuals training needs due to the variables of the sex of the teacher and the number of years of experience differences